Digital Technology Utilization by Beginner Hikers: Safety and Technopreneurship Perspectives in Nature Tourism - Muhamad Reza Tediantoro; Nanang Hoesen Hidroes Abbrori (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
This study analyzed digital technology utilization by beginner hikers to propose a safety-driven platform architecture integrating outdoor risk management and local technopreneurship. The research was motivated by recurring field vulnerabilities in beginner-friendly mountains, utilizing a multiple-case representation of Mount Gamkonora and Mount Prau. These locations represented contrasting profiles: unmapped, infrastructure-limited terrains versus highly accessible open-trip environments. Despite their differences, both destinations shared critical safety gaps, including navigational deficits and the dangerous bypass of pre-hike physical readiness assessments. A descriptive qualitative approach was employed through semi-structured interviews with eight beginner hikers. The thematic analysis revealed severe navigation difficulties, limited supporting facilities, managerial deficits in commercial trips, and an urgent need for offline-accessible information. Findings demonstrated that these hazards could be mitigated through smart tourism technologies, specifically utilizing offline maps, virtual basecamps, automated physical supply calculators, and verified local service marketplaces. This study concluded that localizing digital solutions effectively addressed immediate physical and psychological hazards while generating sustainable economic value for local communities.